2022
DOI: 10.1208/s12248-021-00676-9
|View full text |Cite
|
Sign up to set email alerts
|

Nano/microparticle Formulations for Universal Influenza Vaccines

Abstract: Influenza affects millions of people worldwide and can result in severe sickness and even death. The best method of prevention is vaccination; however, the seasonal influenza vaccine often suffers from low efficacy and requires yearly vaccination due to changes in strain and viral mutations. More conserved universal influenza antigens like M2 ectodomain (M2e) and the stalk region of hemagglutinin (HA stalk) have been used clinically but often suffer from low antigenicity. To increase antigenicity, universal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Nano‐vaccine technology involves encapsulation of antigens into nanoparticles or the displaying antigens on their surface. This approach protects antigens from premature proteolytic degradation, improves stability, possesses good adjuvant properties, facilitates targeted delivery and controls their release, leading to enhanced antigen presentation, and subsequently results in increased vaccine antigenicity and immunogenicity [ 50 , 51 ]. A study demonstrated that two‐component nanoparticles that co‐display diverse influenza HA trimers induced broadly protective antibody responses to heterologous viruses in mice, ferrets and nonhuman primates (NHPs) [ 52 ].…”
Section: Universal Vaccine Platformsmentioning
confidence: 99%
“…Nano‐vaccine technology involves encapsulation of antigens into nanoparticles or the displaying antigens on their surface. This approach protects antigens from premature proteolytic degradation, improves stability, possesses good adjuvant properties, facilitates targeted delivery and controls their release, leading to enhanced antigen presentation, and subsequently results in increased vaccine antigenicity and immunogenicity [ 50 , 51 ]. A study demonstrated that two‐component nanoparticles that co‐display diverse influenza HA trimers induced broadly protective antibody responses to heterologous viruses in mice, ferrets and nonhuman primates (NHPs) [ 52 ].…”
Section: Universal Vaccine Platformsmentioning
confidence: 99%
“…Surface modifications with hydrophilic polymers such as PEG are essential for reducing nonspecific interactions with serum proteins, decreasing susceptibility to opsonization, and deferring uptake by phagocytosis, thereby expanding the drug half-life and further affecting the biodistribution and pharmacokinetic profile of the drug, and are thus considered the 'gold-standard' of cloaking agent systems. Polymeric nanoparticles can be divided into two types: nanocapsules and nanospheres [54].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…These are made up of an inner hydrophobic core (which can include medications that are poorly water soluble) and an exterior hydrophilic polymer (such as PEG, which can extend circulation time and improve accumulation). Polymeric micelles, for example, have received a lot of interest as drug delivery agents with substantial therapeutic promise [54]. One of the most appealing nanotechnologies for improving the water solubility and stability of otherwise technologically constrained (poorly water soluble and unstable) pharmaceuticals is drug encapsulation with polymeric micelles.…”
Section: Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza A virus will remain a significant threat to global public health for the foreseeable future due to its ability to constantly evolve and generate new variants [1]. The segmented RNA genome and a broad host range critically contribute to the IAV evolution, which has prevented the development of a universal vaccine so far and reduces the efficacy of available vaccines and increases the potential of the emergence of antiviral drug resistance [2,3]. Now, there is emerging evidence that IAV could have a mutualistic relationship with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and cause simultaneous flu and coronavirus disease 2019 (COVID-19) and epidemics in humans [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%